International Criminal Trials Creating a Dominate Narration of History and Overlooking Historical Blind Spots - El Masry, Hoor (AUC Knowledge Fountain, 2023)
History is key to developing a better understanding of the world, what has happened in the past helps one understand the present. Understanding and studying history helps one understand the identity of his country and other countries as well. History can be the link to understanding and connecting events. You can understand why Israel is hated by Arabs when you study the history of its creation. The definition and the determination of history itself are complicated. Regardless of how major the event you are learning about, history remains the stories which are narrated about this specific event. Historians support these stories with credible sources, transforming them from stories and tales to history. If this history was narrated from a different source, not a historian but a legal entity a criminal court for instance, there comes the entanglement between history writing and international criminal law. Some historical narratives are created by international criminal tribunals prosecuting mass atrocity and the historical function of these tribunals is then undeniable. At this point, one of the functions of international criminal courts would be producing historical records concerning both the accused and the broader mass atrocity to which they are alleged to have contributed1. As Fergal Gaynor stated, "Any trial involving top military or political leaders, where the trial record incorporates thousands of documents and the testimony of hundreds of witnesses, can hardly avoid creating a historical record"2. History has several components, features, and characteristics to allow the production of a credible historical narrative, which shall be discussed further in Chapter 1 of this research. Criminal international trials also have several components, features, and characteristics to allow the production of a fair verdict and to ensure the delivery of the rights of the accused. The features and the components of international criminal trials are not constructed to produce a historical narrative about the atrocity. This itself may cause the produced narrative to be flawed and this is argued by many historians and scholars, this produced narrative may be considered bad history. One may then assume that historical narratives produced by international criminal tribunals is a collateral damage and is far from being the objective of these tribunals; accordingly, one would be unjust to criticize these narrations as they are far from being the objective of the tribunals. These narrations are then built on the assumption of the existence of a certain mass atrocity, if we take the ICTR as the discussed example in this research, the mere creation of the tribunal was to trial those accused of the genocide in Rwanda. Accordingly, when the tribunal was created it had already assumed that genocide had occurred, but the trial itself was trialing those accused of the genocide; what would have happened if the tribunal hadn't convicted anyone? Would this mean that the genocide has not occurred? In this research I argue the exact opposite of the assumed bad history, I argue that the produced historical narrative is one of the main objectives of these tribunals because the atrocities that have been committed are too grave that no punishment can be equivalent to the committed genocide, war crimes or crimes against humanity. What can be achieved is producing a historical narrative from the perspective of those controlling the trial, that would be dominant and would uphold the perspective of the victims about the massacre. Even if the produced narration was limited since its produced by a legal tribunal and even if the produced narration and the tribunal limitation were found to be biased, this bias may not be dreadful or unwelcome. The source of this bias, its elements, its effect, and its consequences are what need to be discussed, recognized, and then evaluated.